A roadmap for achieving health equity in India: A proposed framework and assessment of the determinants of health equity - Ota, Rachita; Agrawal, Supriti; Sarkar, Purnima (Indian Journal of Community Health, 2018)
With the upcoming technical interventions in the health sector of India, India has been able to create a great scope for Medical Tourism in the country. People from different nations are coming to India to avail many critical treatments at an affordable price. Even after such great development, Health Equity has always been a great challenge for our country. Through Health Equity, we mean availing the standard health services by the under-privileged, marginalized group of people compared to the privileged segment of the community. The present study will help us to highlight on the prioritization of the allocation of the resources to the most eminent tier of the Health care structure. Also, this study will focus on the effectiveness of this component of the Health care structure of India and how this can help in throwing light on the disparity of the health care services through a proposed model.